Synergistic action between peptide-neomycin conjugates and polymyxin B against multidrug-resistant gram-negative pathogens - Story, Sandra; Jiang, Liuwei; Leutou, Alain S.; Arya, Dev P. (Frontiers in Microbiology, 2025)
Globally, it is predicted that by 2050, 10 million people will die annually because of infections with drug-resistant bacteria. Since antibacterial agents with novel mechanisms of action have not been developed in the past 30 years, there has been a surge of interest in combination therapies using existing drugs. The combination of aminoglycosides and colistin is often used to treat pneumonia caused by multidrug-resistant bacteria. The goal of this study is to investigate the relationship between the antibacterial activity of a peptide-neomycin library and polymyxin B in extensively drug-resistant and pandrug-resistant bacteria. The peptide-neomycin library contained conjugates with one or two amino acids linked to neomycin, rendering them unsuitable substrates for aminoglycoside-modifying enzymes. Neomycin- susceptible and neomycin-resistant members of Acinetobacter baumannii, Klebsiella pneumoniae, and Pseudomonas aeruginosa were screened for synergy with polymyxin B using two-way checkerboard and time-kill methods. Most A. baumannii strains are resistant to amikacin, gentamicin, tobramycin, and plazomicin, and approximately half are susceptible to neomycin. P. aeruginosa strains have a similar resistance profile but was more susceptible to plazomicin. K. pneumoniae strains are most susceptible to a wide variety of aminoglycosides. Bacteria challenged with a combination of neomycin, other aminoglycosides, and polymyxin B exhibited an additive to indifferent relationship, whereas synergy was found with several neomycin-peptide conjugates containing cysteine, arginine, or tryptophan, lowering the minimal inhibitory concentration for the peptide-neomycin conjugate by 8-64-fold and polymyxin B by 2-8-fold. Cysteine, arginine, or tryptophan conjugates were the most effective against A. baumannii and K. pneumoniae carrying a 16S rRNA methyltransferase gene and a pandrug-resistant P. aeruginosa strain. Resistance to the combination of R-, C-, or RC-NEO conjugates and PB did not develop over a 14-day period in neomycin-susceptible strains of A. baumannii, K. pneumoniae, and P. aeruginosa. Based on this survey of the peptide-neomycin library, circumvention of aminoglycoside-modifying enzymes and alluding to bacterial resistance is an important step toward the design and development of peptide aminoglycoside-based motifs for antimicrobial drug development.